2005
DOI: 10.1159/000086679
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis Mortality in the United States, 1979–2001

Abstract: The etiology of nonfamilial amyotrophic lateral sclerosis (ALS) remains unknown. Earlier studies have suggested an increase in the incidence of ALS over time. We performed a retrospective analysis of ALS-associated death rates and trends in the United States for 1979–2001 using death records from the national multiple cause-of-death database. The US average annual age-adjusted ALS death rate was 1.84 per 100,000 persons for 1979 through 1998. Most deaths were among adults ≧65 years of age and the median age at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 60 publications
(49 reference statements)
7
58
0
4
Order By: Relevance
“…This is consistent with previous US mortality studies of MND and ALS [11,12,18]. A recent review of global ALS epidemiology showed a trend of ALS incidence to increase with higher latitudes among European countries [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous US mortality studies of MND and ALS [11,12,18]. A recent review of global ALS epidemiology showed a trend of ALS incidence to increase with higher latitudes among European countries [19].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, rates by subpopulations showed elevations among males and whites that increased with age until approximately 70-79 years. These subpopulations also had increased rates in previous studies of ALS mortality in the United States [11,12]. The fact that ALS incidence and prevalence is greater among men has been a consistent finding across studies [13].…”
Section: Discussionsupporting
confidence: 55%
“…In the United States, a retrospective study described rates increasing from 1.7/100,000 inhabitants in 1979, to 1.9/ 100,000 inhabitants in 2001 10 . Studies from other Countries also suggest this trend, raising the epidemiological interest regarding putative causes for the regional discrepancies, as well as risk factors for ALS overall 1,2,8,10 . In Brazil, the magnitude, as well as mortality rates of ALS are poorly studied.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Many of these studies analyzed large geographic areas with unstable populations, creating methodological challenges with respect to ABSTRACT: Objective: Previous studies have suggested that the incidence of amyotrophic lateral sclerosis (ALS) in Nova Scotia is relatively high and increasing over time. This study was performed to determine the current incidence of ALS in Nova Scotia and to compare this to data collected in 1984 and 1995.…”
mentioning
confidence: 99%